Development of Interactive Learning Media using Adobe Animate for Computational Thinking Materials - Dwinanto, Arif; Bouty, Abd. Aziz; Latief, Mukhlisulfatief; Novian, Dian; Rijal, Bait Syaiful; Rambing, Ilsan (Jambura Journal of Informatics, 2024)
Based on initial observations conducted at SMA Negeri 1 Tilamuta, researchers found several problems in the learning process, including students often leaving the classroom during lessons and having difficulty understanding the material given by the teacher. The purpose of this study was to determine how to develop interactive learning media, to determine the feasibility test in media development, and to determine the practicality test or user response. The method used in this study is R&D (Research and Development) with the ADDIE approach model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. The results of the feasibility test in the interactive learning media validity test category for media experts are in the "very feasible" category with a percentage of 92%, and material experts are also in the "very feasible" category with a percentage of 90%, and the results of the practicality test or user response to interactive learning media on computational thinking material are in the "very feasible" category with a percentage value of 94%.